Formation of self-organization skills of future trainers based on a synergic approach - Kolyada M.G.; Gorbachev S.S.; Belykh S.I.; Donichenko E.Yu. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to theoretically substantiate the formation of self-organization skills of future coaches based on a synergetic approach. Methods and structure of the study. Analysis of the training process based on a synergetic approach is presented as a complexly organized system, within the framework of which conditions for self-learning, self-development, self-realization, etc. are created. Training during training becomes interactive, and the trainer-teacher and the student learn from each other. Results and conclusions. Features of the activity of a teacher (trainer-teacher) within the framework of the synergetic approach are that he must: - create a stimulating learning environment that will allow future trainers to develop their self-organization skills; - use productive teaching methods that activate the participation of future trainers in the process of self-organization; - act as a facilitator who supports and guides the process of self-organization of future trainers; - take into account the individual needs and characteristics of each future coach in order to create a personalized training route; - promote the development of reflection and self-esteem skills among future trainers; - encourage cooperation and exchange of experience between students. In technological and methodological terms, the synergetic approach involves a problem-oriented approach to the presentation of educational and training material, the use of so-called resonant teaching methods and their individual psychological and pedagogical support.